Phagocytosis of immunoglobulin-coated emulsion droplets. (May 2015) - Ben M'Barek, Kalthoum; Molino, Diana; Quignard, Sandrine; Plamont, Marie-Aude; Chen, Yong; Chavrier, Philippe; Fattaccioli, Jacques
Abstract: Phagocytosis by macrophages represents a fundamental process essential for both immunity and tissue homeostasis. The size of targets to be eliminated ranges from small particles as bacteria to large objects as cancerous or senescent cells. Most of our current quantitative knowledge on phagocytosis is based on the use of solid polymer microparticles as model targets that are well adapted to the study of phagocytosis mechanisms that do not involve any lateral mobility of the ligands, despite the relevance of this parameter in the immunological context. Herein we designed monodisperse, IgG-coated emulsion droplets that are efficiently and specifically internalized by macrophages through in-vitro FcγR-mediated phagocytosis. We show that, contrary to solid polymeric beads, droplet uptake is efficient even for low IgG densities, and is accompagnied by the clustering of the opsonins in the zone of contact with the macrophage during the adhesion step. Beyond the sole interest in the design of the material, our results suggest that lateral mobility of proteins at the interface of a target greatly enhances the phagocytic uptake.